Human resource management in sport and recreation - Chelladurai, Packianathan PhD; Kerwin, Shannon 1981- (Human Kinetics, 2017)
Human Resource Management in Sport and Recreation, Third Edition, provides current and future practitioners with a solid foundation in research and application of human resource management in the sport and recreation industries. With more than 50 collective years of experience in teaching management of human resources, Packianathan Chelladurai and Shannon Kerwin synthesize the core dynamics of human resources as well as the role of sport managers and recreation managers. This third edition's updated references examples, and studies reflect the increased growth, interest, and complexity in human resource management in sport and recreation in recent years. Additional enhancements of the third edition include the following: A greater emphasis on recruitment and training as an essential component of success; New Technology in human resource management and diversity management of human resources sidebars to connect theory to practice for sport managers as they confront contemporary issues in the workplace; Case studies at the end of each chapter to help students apply concepts from the chapter to real-world scenarios; Updated pedagogical aids-learning objectives, summaries, list of key terms, comprehension questions, and discussion questions-to guide students learning through each chapter.